Department Head Perceptions of the Need for Distance Education In the Agricultural Sciences - Blannie E. Bowen; Joan S. Thompson (Journal of Applied Communications, 1995)
The assessment was requested by AG*SAT, a consortium of land-grant universities created to plan, coordinate, and deliver distance education in the agricultural sciences.